Psychological defense mechanisms and use of corporeal discourse: a comparison between patients with irritable bowel syndrome, medical personnel and healthy volunteers. Issue 4 (17th September 2020) - Reicher-Atir, Rebecca; Avnat-Becker, Lee; Levy, Sigal; Sperber, Ami D.; Dickman, Ram
Abstract : Objective: The aim of this study was to compare the use of psychological defense mechanisms and corporeal discourse among patients with irritable bowel syndrome (IBS), medical personnel and healthy volunteers. Methods: All participants completed an identical battery of questionnaires: a demographic questionnaire, the Corporeal Discourse Questionnaire, the Defense Style Questionnaire and a Visual Analogue Scale for situational anxiety and depression. Patients and medical personnel were recruited from the Rabin Medical Center, a tertiary university-affiliated hospital. Findings were analyzed according to the study variables and compared among the groups. Results: Questionnaires were completed by 40 patients with IBS, 39 medical personnel and 40 healthy volunteers. Correlations between the study variables within the entire study group (all study participants, N = 119) revealed that corporeal discourse was found to be significantly correlated with the immature and neurotic class of defense mechanisms ( r = 0.41, P < 0.01 and r = 0.20, P < 0.05, respectively), depression ( r = 0.46, P < 0.05) and anxiety ( r = 0.46, P < 0.05). Differences between IBS and the other two groups were significant for corporeal discourse, depression, anxiety and use of immature defense mechanisms. Posthoc analyses showed that medical personnel differed from IBS patients in all of these measures. Healthy volunteers had an inconsistent pattern of differences from the other two groups. Conclusion: Maturity level of defense mechanisms and the tendency to use corporeal discourse are expressed among IBS patients in a diverse and unique manner. These findings may indicate additional psychological mechanisms that could explain the use of somatic complaints in IBS and support the implementation of tailored psychological interventions.